Efficacy of Laser versus Formocresol and Ferric Sulphate for Pulpotomy in primary Molars: A Randomized Clinical Trial. - Gul, Madiha; Abu Bakar Sheikh; Shahid Islam; Azam Muhammad Aliuddin; Nina Ayaz; Farwa Sajjad (International Journal of Endorsing Health Science Research, 2025)
Background: To compare post-operative pain outcomes following pulpotomy using diode laser, formocresol, and ferric sulphate in primary molars of paediatric patients, assessed through the Wong-Baker Faces Pain Rating Scale (WBS). Methodology: A randomized clinical trial was conducted at Fatima Jinnah Dental College and Hospital, Karachi, from January to August 2023. Ninety children aged 4–9 years requiring pulpotomy were enrolled and randomly allocated into three groups (n = 30 each). Group 1 received formocresol, Group 2 ferric sulphate, and Group 3 diode laser treatment. Post-operative pain was evaluated at 2 weeks, 4 weeks, 3 months, 6 months, and 12 months. Results: Laser pulpotomy demonstrated the lowest pain scores (WBS = 0.07 ± 0.37) at 2 weeks, compared with formocresol (2.93 ± 3.14) and ferric sulphate (2.20 ± 2.54) (p < 0.001). Differences remained significant at 4 weeks but not beyond 3 months (p > 0.05). Radiographic success rates were highest for diode laser (100%), followed by ferric sulphate (95%) and formocresol (90%). No major adverse events were observed. Conclusion: Diode laser pulpotomy produced superior early pain relief and excellent clinical outcomes compared to conventional pulpotomy medicaments. It represents a safe, minimally invasive, and effective alternative for managing vital pulp therapy in paediatric dentistry.